Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

There's a problem (#10.23) in Apostol's Mathematical Analysis of which I am having a rough time solving: Let $F(y)= \int_{0}^{\infty}\frac{\sin xy}{x(x^{2}+1)}dx$ if $y > 0$. Show that $F$ satisfies the differential equation $F''(y)-F(y)+\frac{\pi }{2} = 0$ and deduce that $F(y)= \frac{1}{2}\pi(1-e^{-y})$. Use this result to deduce the following equations, valid for $y > 0$ and $a > 0$: Use this to deduce that for $y>0$ and $a>0$ \begin{align} \int\nolimits_{0}^{\infty}\frac{\sin xy}{x(x^{2}+a^{2})}dx = \frac{\pi}{2a^{2}}(1-e^{-ay}), \newline \int_{0}^{\infty}\frac{\cos xy}{x^{2}+a^{2}}dx = \frac{\pi e^{-ay}}{2a}, \newline \int_{0}^{\infty}\frac{x\sin xy}{x^{2}+a^{2}}dx = \frac{\pi}{2}e^{-ay} \end{align} We could use $\int_{0}^{\infty}\frac{\sin x}{x}dx = \frac{\pi}{2}$

How can I show this?

share|cite|improve this question
You can use dollar signs to get your tex code compiled. – Rasmus Apr 20 '11 at 21:39
this problem has multiple parts. Which one are you stuck at? – Alon Amit Apr 20 '11 at 21:43
Which parts do you have trouble with? – Rasmus Apr 20 '11 at 21:43
This is posted as an answer to a previous question:… . – Raeder Apr 20 '11 at 21:57
@user9848: Assume all the nice things like swapping the derivative with the integral etc. Are you having trouble with justifying this or with the algebra part? – user17762 Apr 20 '11 at 22:35
up vote 5 down vote accepted

Let $f(x,y)=\frac{\sin(xy)}{x(x^2+1)}$. Then $$f_{yy}(x,y)-f(x,y)=-\frac{x\sin(xy)}{x^2+1}-\frac{\sin(xy)}{x(x^2+1)}=-\frac{\sin(xy)}{x}$$ It follows that $$F''(y)-F(y)=\int_0^\infty -\frac{\sin(xy)}{y} dx=-\int_0^\infty \frac{\sin(xy)}{xy} \,d(xy)=-\pi/2$$ Then $F(y)$ is a solution to the differential equation $z''-z+\frac{pi}{2}=0$. It follos that $F(y)=ae^y+be^{-y}+\frac{\pi}{2}$. From the definition of $F(y)$ one can check that $\lim_{y\to 0} F(y)=0$ and $\lim_{y\to 0} F'(y)=\pi/2$. Then $a+b+\pi/2=0$ and $a-b=\pi/2$. Solving for $a$ and $b$ we have $a=0$ and $b=-\pi/2$. Therefore $$F(y)=\frac{\pi}{2}(1-e^{-y})$$. Let $$G(y):=\int_{0}^{\infty}\frac{\sin xy}{x(x^{2}+a^{2})}dx.$$By substitution $t=x/a$ one can show that $G(y)=\frac{F(ay)}{a^2}=\frac{\pi}{2a^2}(1-e^{-ay})$ and then $$\begin{align*}G'(y)&=\frac{F'(ay)}{a}=\frac{\pi e^{-ay}}{2a}\\G''(y)&=F''(ay)=-\frac{\pi}{2}e^{-ay}\end{align*}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.